The Effect of Operational Efficiency on Café Performance - Saragih, Ramadian Maghvira; Nurbaiti, Nurbaiti; Nasution, Muhammad Irwan Padli (Journal of Social Work and Science Education, 2025)
This study focuses on the problem of operational efficiency which is often an obstacle in improving café performance, especially in Café Hitado and Café Distro in Serdang Bedagai. Suboptimal operational efficiency often hinders the café's ability to reduce costs, increase productivity, and maintain competitiveness amidst tight industry competition. This study aims to analyze the effect of operational efficiency on café performance through various aspects such as stock management, service, and human resource management. The research method used is a descriptive qualitative approach, with data collected through direct observation, in-depth interviews with management and staff, and documentation of operational records and sales reports. Data analysis was carried out through the process of reduction, presentation, and drawing conclusions to identify patterns and relationships between operational efficiency and café performance. The results of the study show that operational efficiency in Café Hitado and Café Distro improves customer service and satisfaction. Café Hitado prioritizes the preparation of interactive materials and events, while Café Distro focuses on personal communication and friendliness. This strategy supports customer loyalty, positive reputation, and competitive business performance in a dynamic market.